Rapid Induction of Ageing Character in Brandy Products – Part I. Effects of Extraction Media and Preparation Conditions - van Jaarsveld, F.P.; Hattingh, S.; Minnaar, P.; Blom, M. (South African Journal of Enology and Viticulture, 2016)
The purpose of this study was to investigate the use of different wood types and treatments, and extraction media to induce rapid ageing of brandy. Extracts were prepared from American and French oak, specially prepared and supplied by a cooper, and from commercially obtained oak; both representative of different toasting levels, including untoasted, light, medium and heavy toasted. To extract the wood components, wood chips in either 55% (v/v) neutral wine spirits or water media were boiled under reflux. Distillation was followed by either open (higher boiling temperature) or closed (vacuum or reduced pressure – lower boiling temperature) concentration of the decanted solvent by 45, 65 and 85% (v/v). The concentrated extracts were fortified. Screened extracts were added to unmatured pot-still brandy and aged for eight months at room temperature in glass containers. Controls were stored below 0°C. Matured and unmatured (control) pot-still brandy samples were analyzed for wood-derived congeners by means of HPLC and GC. This article focuses on the effects of the extraction media, and on level and method of concentration (open and reduced pressure) on sensory quality and chemical composition. The treatments that gave acceptable extracts, and the best overall quality pot-still brandy were those that entailed (1) using ethanol instead of water as extraction medium, and (2) levels of concentration above 45% (v/v). Open and reduced-pressure concentrations showed little difference in the quality of the products yielded. Treatments yielding the most acceptable extracts and best overall quality pot-still brandy generally also contained higher concentrations of volatile and less volatile wood-derived congeners. Multivariate data analysis was conducted on the pot-still brandy samples representing the different treatments. Discriminate analysis provided better separation of samples than principal component analysis.